2022
DOI: 10.52965/001c.38954
|View full text |Cite
|
Sign up to set email alerts
|

Chaperones Utilization in Clinical Practice: Intimate and Sensitive Physical Examination Best Practice Strategies and Concepts in Modern Urological Medicine

Abstract: The intention of utilizing chaperones during sensitive physical exams is to show respect to the patient, while simultaneously providing protection to both the patient and the medical provider. Despite clinical practice recommendations to offer chaperones for sensitive urologic exams, there is no data regarding the consistency of chaperone utilization. Our aim was to summarize the patient and provider perspectives on the role of chaperones in urology as well as identify barriers to implement chaperone consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 17 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…Patient trust is important; prior studies have demonstrated that those with less trust in their physician are more likely to report complaints that their needs or services were not met during an office visit. 3,4,7 Offering a chaperone is seen as a sign of courtesy and respect even though many patients do not prefer to have one. 1 This is an opposing view to physicians, most of whom prefer the use of chaperones.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Patient trust is important; prior studies have demonstrated that those with less trust in their physician are more likely to report complaints that their needs or services were not met during an office visit. 3,4,7 Offering a chaperone is seen as a sign of courtesy and respect even though many patients do not prefer to have one. 1 This is an opposing view to physicians, most of whom prefer the use of chaperones.…”
Section: Discussionmentioning
confidence: 99%
“…No doubt, false accusations can damage a physician's reputation and cause a great deal of stress that can last for a long time. 4,7 Documentation is a great asset in providing the evidence for chaperone use. 1,2,5,6,8 The lack of such documentation does not necessarily mean that a chaperone was not present, but it is a real concern that needs to be raised to improve the standard of patients' care and to provide evidence and support to clinicians.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations